An unusual case of undifferentiated pleomorphic vulval sarcoma - Jaiswal Riddhi; Deval Brajesh Dubey; Anjoo Agarwal (Barpeta Obstetrics and Gynaecological Society, 2023)
Vulvar sarcomas are one of the rarer female genital tract malignancies, characterized by nonspecific signs and symptoms often leading to clinical misdiagnosis which increases the morbidity and mortality. It presents in 5th to 6th decade of life. Undifferentiated pleomorphic sarcomas (UPS) previously known as malignant fibrous histiocytoma (MFH) are the rarest of vulval sarcomas and hence least suspected initially. It is advised to keep vulvar sarcomas as a clinical differential in cases of non specific vulval swellings in order to establish an early accurate diagnosis to expedite its management. We present an unusual and rare case which was clinically misdiagnosed as a benign vulval swelling in a 26 year old married female who presented with painless vulval swelling for 1 year. It was provisionally diagnosed as malignant mesenchymal neoplasm on fine needle aspiration cytology which later was confirmed as UPS on after evaluating a judicious panel of immunohistochemistry markers where a myogenic, vascular and neurogenic origin was ruled out. Patient was treated with wide local excision and adjuvant platinum based chemotherapy which showed good response with no signs of reoccurrence or metastasis in a follow up period of 6 months.